(untitled) (International Journal of Built Environment and Sustainability, 2023)
Design based on performance and energy efficiency is important in residential buildings. The design approach, which considers climatic data and energy conservation, was also used in traditional building design. In this context, it is aimed to evaluate the Karakurt houses in Kars, built during the Russian occupation period (1878-1918) in Turkey, within the scope of climate-sensitive design. The inadequacy of studies in the literature on Kars Karakurt houses, which are traditional architectural examples that preserve the original texture of the region as qualified representatives of Baltic architecture, constitutes a research gap. In this study, qualitative and quantitative research methods were used. The architectural plan and facade typologies of the buildings in Karakurt village were obtained by measuring techniques and tools. In the qualitative research part, information about the buildings was obtained from on-site investigations and a situation analysis was made. In the quantitative research part, orientation analyses of buildings and spaces, and window-wall area ratios of facades have been evaluated according to climate-sensitive design approaches. In the research findings, design criteria such as plan, facade, roof and material properties of 10 Karakurt houses, were examined and it was seen that the buildings were standardized within the scope of climate-sensitive design. It is seen that the north direction, where the wind is dominant and the sunlight penetration is the least, is not preferred for the orientation of the buildings and the space, and the window/wall area ratio is kept to a minimum, reducing the energy loss especially due to the openings.